Use of cumulative summation (CUSUM) as a tool for early feedback and monitoring in robot-assisted radical prostatectomy outcomes and performance - Chan, Garson; Pautler, Stephen E. (Canadian Urological Association Journal, 2018)
Introduction: Today’s surgical practice has evolved, with increasing emphasis on quality assurance. Many forms of quality-control monitoring have been suggested, but they are often impractical or difficult to implement. Cumulative summation (CUSUM) is a simple method to provide visual feedback before significant quality issues arise. We present our initial use and practical application of CUSUM in a surgical practice. Methods: A retrospective analysis was applied to a prospectively collected database of 577 sequential patients who have undergone robot-assisted radical prostatectomy from a single surgeon over a 10-year period. Outcome measures were analyzed with CUSUM, which included a composite complication score, continence rates, length of hospital stay, biochemical recurrence, and need for adjuvant radiation. If any outcomes were out of control, they would cross the CUSUM failure line. Results: CUSUM chart-plotting for incontinence demonstrated an initial upward slope followed by trending to a new safety limit. Additionally, outcomes in complications and biochemical recurrence did not reach the established safety boundaries. Length of stay and radiation outcomes did initially cross the safety line, but were improved over time. Conclusions: The use of CUSUM in clinical practice can fulfill the need for quality assurance. CUSUM plotting in our practice reflected the initial learning curve, followed by ongoing maintenance and improvement in performance. These changes were consistent with the implementation of changes in surgical techniques. Although this tool was used retrospectively, this strengthens our argument to implement the tool prospectively and assess real-time refinement of surgeon skill. We have demonstrated that CUSUM can be appropriately used to assure quality control in a surgical practice.